Self-assembly of bacterial amyloid protein nanomaterials on solid surfaces - Onur, Tugce; Yuca, Esra; Olmez, Tolga Tarkan; Seker, Urartu Ozgur Safak (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
Hypothesis: Amyloid-forming biofilm proteins of Escherichia coli, namely CsgA and CsgB, can form self-assembled nanofibers on solid surfaces. These proteins can be programmed to form bio-nanomaterials for functional applications. Experiments: In this study, the assembly of the CsgA and CsgB protein on solid surfaces was investigated in real time using a quartz crystal microbalance instrument with dissipation monitoring. The assembly kinetics of the CsgA and CsgB proteins in various settings on solid surfaces were investigated. Protein nanowires were investigated using electron microscopy. Findings: CsgA protein polymers and CsgB-added CsgA polymers form densely packed biofilm on gold surfaces, whereas CsgB polymers and CsgA-added CsgB polymers form biofilms with high water-holding capacity according to the dissipation data. Electron microscopy images of nanofibers grown on gold surfaces showed that CsgA and CsgB polymers include thicker nanofibers compared to the nanofibers formed by CsgA-CsgB protein combinations. The resulting nano/microstructures were found to have strong fluorescence signals in aqueous environments and in chloroform while conserving the protein nanowire network. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Bacterial biofilm proteins; Curli; Amyloids; Nanomaterials; QUARTZ-CRYSTAL MICROBALANCE; ESCHERICHIA-COLI; MECHANICAL-PROPERTIES; ENGINEERED CELLS; CORE STRUCTURE; QCM-D; FIBRILS; DISSIPATION; ATTACHMENT; NANOFIBERS; Chemistry